Influence of Rice Husk Ash on the Swelling and Strength Characteristics of Expansive Soil - Jain, Arpit; Choudhary, Anil Kumar; Jha, J. N. (Geotechnical and geological engineering, 2020)
Black cotton soils are expansive soils which exhibit high swelling and shrinking when exposed to changes in moisture content. Durability of structure resting on expansive clays is always in question due to swelling/shrinkage of such clays. The performance of paved and unpaved road pavements constructed over such expansive soil subgrades is often poor and in most cases show cracking, potholes, wheel path rutting, serious differential settlements and heaving in various locations. In addition to problems related to expansive soils another problem arising in all developing and developed countries is due to the wastes generated from various activities which not only cause severe environmental problems, but also occupy a huge area of land for its disposal. Rice husk ash (RHA) is one such wastes produced from the burning of rice husk and if used as an additive to expansive soil shall not only significantly reduce the swelling/shrinkage characteristics of such soils but also solve the environmental and disposal problems being created by the ash. The paper presents the results of an experimental investigation conducted to study the effect of RHA on swelling, shrinkage and compaction characteristics of the expansive soil. The RHA was mixed with expansive soil in varying proportions. Free swell index, Atterberg limits, light compaction tests, unconsolidated undrained triaxial compression tests, California bearing ratio tests were carried out with specimens containing varying percentages of RHA. It is concluded that addition of RHA in appropriate proportions not only reduces the swelling and shrinkage behavior of expansive soil significantly but also makes it more stable.